Agricultural drought : Assessment & monitoring - SAI, M. V. R. SESHA; MURTHY, C. S.; CHANDRASEKAR, K.; JEYASEELAN, A. T.; DIWAKAR, P. G.; DADHWAL, V. K. (MAUSAM, 2016)
Drought is a creeping natural disaster with long lasting effects on ecology as well as economy. Monitoring and assessment of drought is a very critical component of the drought management strategy aimed at mitigation of its adverse impacts. Spatial extent, intensity and duration of drought related information is essentially needed for taking the choicest rational decision making in the field of agriculture. Satellite remote sensing enables deriving indicators that explain the prevalence, severity, persistence and spatial extent of the area affected by drought. New satellite missions coupled with novel information extraction techniques are opening new vistas towards monitoring and assessment of drought. Aspects related to agricultural drought are discussed in this paper.